Desulfovibrio bacteria enhance alpha-synuclein aggregation in a Caenorhabditis elegans model of Parkinson’s disease - Huynh, Vy A.; Takala, Timo M.; Murros, Kari E.; Diwedi, Bidhi; Saris, Per E. J. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The aggregation of the neuronal protein alpha-synuclein (alpha-syn) is a key feature in the pathology of Parkinson’s disease (PD). Alpha-syn aggregation has been suggested to be induced in the gut cells by pathogenic gut microbes such as Desulfovibrio bacteria, which has been shown to be associated with PD. This study aimed to investigate whether Desulfovibrio bacteria induce alpha-syn aggregation. Methods Fecal samples of ten PD patients and their healthy spouses were collected for molecular detection of Desulfovibrio species, followed by bacterial isolation. Isolated Desulfovibrio strains were used as diets to feed Caenorhabditis elegans nematodes which overexpress human alpha-syn fused with yellow fluorescence protein. Curli-producing Escherichia coli MC4100, which has been shown to facilitate alpha-syn aggregation in animal models, was used as a control bacterial strain, and E. coli LSR11, incapable of producing curli, was used as another control strain. The head sections of the worms were imaged using confocal microscopy. We also performed survival assay to determine the effect of Desulfovibrio bacteria on the survival of the nematodes. Results and Discussion Statistical analysis revealed that worms fed Desulfovibrio bacteria from PD patients harbored significantly more (P<0.001, Kruskal-Wallis and Mann-Whitney U test) and larger alpha-syn aggregates (P<0.001) than worms fed Desulfovibrio bacteria from healthy individuals or worms fed E. coli strains. In addition, during similar follow-up time, worms fed Desulfovibrio strains from PD patients died in significantly higher quantities than worms fed E. coli LSR11 bacteria (P<0.01). These results suggest that Desulfovibrio bacteria contribute to PD development by inducing alpha-syn aggregation.